Acute Truncal Lymphedema Secondary to Axillary Metastatic Melanoma Presenting Like Cellulitis - Shelley J. E. Hwang; Benjamin Y. Kong; Shaun Chou; Deepal Wakade; Matteo S. Carlino; Pablo Fernandez-Penas (Case Reports in Medicine)
There are reported cases of diphencyprone used in treating cutaneous metastases of melanoma. Here, we report a patient with previous primary melanoma on his left back treated with surgical excision and lymphadenectomy, followed by radiotherapy for the recurrent tumor on the primary site. Despite radiotherapy and treatment with dabrafenib and trametinib, in-transit metastases have developed and topical diphencyprone was applied to these metastases. Six weeks later, the patient developed fever and a spreading erythematous tender indurated plaque covering the left side of the body including axillae, back, and flank, clinically suggestive of cellulitis. Systemic antibiotic therapy did not improve the condition and a biopsy showed sparse lymphocytic infiltrate. With the diagnosis of possible acute lymphedema, a CT scan was requested that showed significant axillary lymph node metastasis. The fever was considered secondary to dabrafenib and trametinib therapy. This case highlights that, in patients with lymphadenectomy, atypical forms of lymphedema on the body may appear. Truncal lymphedema is an infrequent event.